Predicting the number of tourists using machine learning - Petrović, Đorđe; Ćebić, Branko; Beljić, Dejan (The Business of Tourism, 2021)
This paper provides an overview of current models of machine learning from time series and their application for the purpose of predicting the number of tourist visits in the coming period. The emergence of the Covid-19 virus has generally had a major impact on Tourism and has introduced great uncertainty in this area. The application of machine learning and an attempt to predict the number of tourist visits in the coming period, can be useful to those who deal with the offer in this area.
Keywords: machine learning; time series; tourism; visits; prediction